2021
DOI: 10.1177/0733464821994703
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Reserve and Driving-Related Cognitive Abilities in a Sample of Oldest Old Drivers Undergoing Assessment of Fitness to Drive

Abstract: This study examines the relationship between age, cognitive reserve (CR), and driving-related cognitive abilities in a sample of oldest old drivers undergoing evaluation of fitness to drive. Structural equation modeling was used to investigate the associations between age, CR, and performances to a standardized set of cognitive tests assessing fitness to drive. Education and work complexity were used as proxy measures of CR. The results showed both measures of CR, but not age, were significantly associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 45 publications
2
5
0
Order By: Relevance
“…The number of conditions leading to restrictions increases with age. This confirms the fourth hypothesis of the study, and these are an indicator of poorer performance in driving tasks as noted by [ 49 ] when comparing drivers with and without restrictions. In particular, drivers with restrictions are those who show a greater decline in cognitive tasks associated with driving four years after being evaluated for the first time compared to drivers without restrictions [ 57 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The number of conditions leading to restrictions increases with age. This confirms the fourth hypothesis of the study, and these are an indicator of poorer performance in driving tasks as noted by [ 49 ] when comparing drivers with and without restrictions. In particular, drivers with restrictions are those who show a greater decline in cognitive tasks associated with driving four years after being evaluated for the first time compared to drivers without restrictions [ 57 ].…”
Section: Discussionsupporting
confidence: 91%
“…This decrease is evident in both men and women. This decline in the performance of driving as well as the cognitive abilities associated with the increase in age has been pointed out in different studies [21,47,48]; although, the big differences between individuals that can be seen in this case must be taken into consideration [20,49]. In this regard, the evaluation of psychophysical abilities in drivers becomes more relevant than chronological age, and these evaluations are more precise at the time of predicting driving performance [20,50].…”
Section: Discussionmentioning
confidence: 87%
“…First, research has consistently shown that cognitive abilities independently explain a significant amount of variance in driving performance [33,34]. Second, there are large individual differences in cognitive abilities even at older ages [32,35]. These results provide evidence in support of a role for the assessment of cognitive functions at an individual level as a more accurate measure of driving ability than chronological age alone [21,32].…”
Section: Introductionmentioning
confidence: 75%
“…Data from a follow-up Australian study showed better results in different cognitive tasks for older drivers than non-drivers and those who stopped driving after 4 years (Anstey et al, 2017). Driving is associated with cognitive reserve (Balzarotti et al, 2021), and various aspects of cognition are affected by normal aging, with great variation among individuals. However, the relationship between cognition and duration of screen time seems to be related to the type of electronic screen.…”
Section: Discussionmentioning
confidence: 99%